KONTRIBUSI SARANA PRASARANA DAN LINGKUNGAN KERJA TERHADAP KINERJA DOSEN DI STAIS DAN STIPER - Muhabibudin, Nur (MPI STAI Sangatta Kutai Timur, 2023)
This research includes quantitative research using a correlational approach. The population in this study were all permanent and non permanent lecturers of STAIS and STIPER about 192 lecturers. This study used a cluster random sampling technique with 67 lecturers as respondents. Test the validity of the data using validity and reliability tests. Prerequisite test analysis using normality test, linearity test, multicollinearity test, and heteroscedasticity test. Hypothesis testing using multiple linear regression test, t-test (partial), and F-test (simultaneous).The results showed that: 1) there is a positive and significant influence of infrastructure facilities on lecturer performance at STAIS and STIPER, evidenced by t-count> table (3.260> 1.998) with a significant level of 0.017 ≤ 0.05. 2) There is a positive and significant effect of the work environment on the performance of lecturers at STAIS and STIPER, as evidenced by t-count> table (2.335> 1.998) with a significant level of 0.023 ≤ 0.05. 3) There is a positive and significant influence of infrastructure and work environment on the performance of lecturers at STAIS and STIPER, evidenced by F-count> F-table (10.222> 3.14) with a coefficient of determination of 0.442 which means it has an influence of 44.2% in the range of sufficient categories. This study concludes that infrastructure and work environment positively and significantly influence the performance of lecturers at STAIS and STIPER East Kutai Regency partially or simultaneously.